Effects of Low Ground Pressure Vehicle Traffic on Tundra at Lonely, Alaska. - Abele,Gunars; Walker,Donald A.; Brown,Jerry; Brewer,Max C.; Atwood,David M. (1978)
Traffic tests were conducted with two low-pressure-tire Rolligon-type vehicles and a small, tracked Nodwell for 1,5, and 10 vehicle passes on tundra near Lonely, Alaska. The traffic impact was limited to compression of the vegetation and the organic mat and a maximum terrain surface depression of several centimeters, with virtually no shearing or disaggregation of the mat. After one year, the visibility of the traffic signatures had increased, surface depression remained the same, and the thaw depth below the multiple pass tracks had increased a few centimeters. (Author)